Informação, memória e lugar: Parque da Lagoa Solon de Lucena - Sousa, Cássio Vinicius Carvalho de (2021)
The Parque da Lagoa has undergone several physical and social transformations since its inauguration in 1939 until the first two decades of the 21st century, which directly influence the urban landscape and the memories produced. In the first urban interventions in the center of the city of João Pessoa, Parque da Lagoa was considered as the nucleus of road layouts and planning. The present research sought to identify the informational potentialities linked to the memorial and patrimonial scenarios, resulting from the physical and social interventions undertaken in the Parque da Lagoa Solon de Lucena. The approach used was predominantly qualitative, as we ponder the interventions seeking to assign meanings. Regarding the objectives, it was a descriptive research, where the characteristics of a phenomenon and the association between variables were illustrated. As a basis for the study, in the first chapter we present reflections on the themes: information, memory, society and heritage, in addition to deepening the relations between memory and place. In the second chapter, we show a narrative of Parque da Lagoa going through its emergence, consolidation and the transformations that occurred throughout its existence. In the final chapters of the dissertation we carry out an analysis of the transformations, the interconnections between the events and reflexions on the strengths and gaps detected in Parque da Lagoa.